SUPERMAJORITIES IN CONSTITUTIONAL COURTS - Rivera León, Mauro Arturo (ROUTLEDGE, 2024)
Constitutional adjudication is a subject of fascination for scholars. Judges may annul the will of a democratically elected Parliament in counter-majoritarian fashion. Although conceived as a remedy against majoritarianism, judges also decide cases by voting. Whether they do so through simple majorities or supermajorities is not trivial. The debate around supermajorities has awakened anew amidst theories of judicial limitation and new conceptions of judicial review. This book advances our knowledge of systems employing supermajorities in constitutional adjudication by performing a comparative analysis of ten jurisdictions and twelve supermajority models. It introduces a typology of the main models of institutional design, the reasons leading policymakers to establish them, and the impact supermajorities have on courts. It explores the question of whether supermajorities grant deference and foster consensus, or if they disable constitutional courts from exercising judicial review. By analyzing the history, practice, and effects of supermajority rules in courts, this book contributes to an ongoing conversation on the democratic implications of voting protocols in constitutional courts. It will be a valuable resource for policy-makers, scholars, and researchers working in the areas of comparative constitutional law and constitutional politics. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 license.